Interaction and potential mechanisms between atorvastatin and voriconazole, agents used to treat dyslipidemia and fungal infections - Xun, Tianrong; Rong, Yan; Lv, Bin; Tian, Jinfei; Zhang, Qing; Yang, Xixiao (Frontiers in Pharmacology, 2023)
Purpose: Atorvastatin (ATO) is combined with voriconazole (VOR) to treating fungal infections in patients with dyslipidaemia in clinical. However, the pharmacokinetic interaction and potential mechanisms between them is unknown. Therefore, this study aimed to investigate the pharmacokinetic interaction and potential mechanisms between ATO and VOR. Patients and methods: We collected plasma samples from three patients after using ATO and VOR. Rats were administered of VOR or normal saline for 6 days and then a single dose of 2 mg/kg ATO and then collected the plasma samples in different time point. The incubation model of human liver microsomes or HepG2 cells were constructed in vitro. A high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) was developed to determined the concentration of ATO, 2-hydroxy, 4-hydroxy-ATO and VOR. Results: In patients, VOR significantly reduced the metabolism of ATO and slowed down the formation of 2-hydroxy and 4-hydroxy-ATO. After being pretreated with oral administration of VOR for 6 days or normal saline and on Day 6, a single dose of 2 mg/kg ATO was administered orally, the t1/2 of ATO is significantly prolonged from 3.61 to 6.43 h, the AUC0-24h values of ATO were increased from 53.86 to 176.84 h.µg.L-1. However, the pharmacokinetics parameters of VOR (20 mg/kg) with or without pretreatment of ATO (2 mg/kg) were in a slight change. In vitro studies indicated that VOR inhibited the metabolism of ATO and testosterone, and the IC50 values were 45.94 and 49.81 μM. However, no significant change in transporter behaviors of ATO was observed when VOR or transporter inhibitors were co-administered. Conclusion: Our study demonstrated that VOR have significant interaction with ATO, which is probably because of the inhibition of the CYP3A4-mediated metabolism of ATO by VOR. Based on the clinically cases and potential interactions, the basic data obtained in our study are expected to help adjust the dose of ATO and promote the design of rational dosage regimens for pharmacotherapy in fungal infections with dyslipidaemia.